2016
DOI: 10.1080/01635581.2016.1206578
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nutritional Status, Inflammatory Condition, and Prognostic Indexes with Postoperative Complications and Clinical Outcome of Patients with Gastrointestinal Neoplasia

Abstract: The aim of this study is to describe and relate nutritional and inflammatory status and prognostic indexes with postoperative complications and clinical outcome of patients with gastrointestinal malignancies. Twenty-nine patients were evaluated; nutritional assessment was carried out by subjective and objective parameters; albumin, pre-albumin, C-reactive protein (CRP), and alpha-1-acid glycoprotein (AGP) were determined. To assess prognosis, the Glasgow scale, the Prognostic Inflammatory Nutritional Index (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…In our study, several inflammatory markers were altered, especially in patients with high weight loss and malnourished, demonstrating that, as marker values were inadequate, inflammation was worse and %WL was higher. Lima et al 16 and Costa et al 19 , and the association between these markers and nutritional status has been previously assessed 14,22 . A recent Asian study of 64 patients with esophageal cancer found a strong association between nutritional status by PG-SGA and performance scores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, several inflammatory markers were altered, especially in patients with high weight loss and malnourished, demonstrating that, as marker values were inadequate, inflammation was worse and %WL was higher. Lima et al 16 and Costa et al 19 , and the association between these markers and nutritional status has been previously assessed 14,22 . A recent Asian study of 64 patients with esophageal cancer found a strong association between nutritional status by PG-SGA and performance scores.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the PG-SGA 24 . Some studies found a positive association between altered CRP levels and weight loss in patients with GIT tumors 16,19,25 . .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the prognostic markers for urogenital cancer and multiple myeloma include elevated values for C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), and the Glasgow Prognostic Score (GPS) [4,9,13,14] . Moreover, several reports have indicated that systemic inflammation plays a critical role in the pathogenesis of malnutrition, weight loss, and muscle loss in cachexia cases [15][16][17][18] . Abdominal computed tomography (CT) and spirometry are routinely performed during preoperative preparations, which allows researchers to calculate psoas major muscle mass and respiratory muscle strength (i.e., peak expiratory flow [PEF]).…”
mentioning
confidence: 99%